Automotive Intelligence Embedded in Electric Connected Autonomous and Shared Vehicles Technology for Sustainable Green Mobility - Vermesan, Ovidiu; John, Reiner; Pype, Patrick; Daalderop, Gerardo; Kriegel, Kai; Mitic, Gerhard; Lorentz, Vincent; Bahr, Roy; Sand, Hans Erik; Bockrath, Steffen; Waldhör, Stefan (Frontiers in Future Transportation, 2021)
The automotive sector digitalization accelerates the technology convergence of perception, computing processing, connectivity, propulsion, and data fusion for electric connected autonomous and shared (ECAS) vehicles, bringing new computing paradigms at the edge with embedded cognitive capabilities into the vehicle domains and data infrastructure to provide holistic intrinsic and extrinsic intelligence for new mobility applications. Innovation occurs predominantly in ECAS vehicles' architectures, intelligent functions, operations, and automotive digital infrastructure. Artificial Intelligence (AI), cellular/wireless connectivity, edge computing, Internet of Things (IoT), Internet of Intelligent Things, digital twins (DTs), virtual/augmented reality (VR/AR) and distributed ledger technologies (DLTs) converge to facilitate vehicle-to-vehicle (V2V), vehicle-to-infrastructure (V2I) and vehicle-to-everything (V2X) communication and automation. Expanding automotive intelligence at the vehicle and mobility system level allows the Internet of Vehicles (IoV) and Internet of Energy (IoE) to become the key enabling technologies to realize future autonomous driving scenarios that embed cognition and autonomous functions. Vehicles become intelligent connected edge micro-servers on wheels, powered by software, smart virtual functions and integrated into the digital infrastructure. Electrification, automation, connectivity, digitalization, decarbonization, decentralization, and standardization are the main drivers that unlock intelligent vehicles' potential for sustainable green mobility applications. ECAS vehicles act as autonomous agents using swarm intelligence to communicate and exchange information either directly or indirectly with each other and the infrastructure, accessing independent services such as energy, high-definition maps, routs, infrastructure information, traffic lights, tolls, parking (micropayments) and finding emergent/intelligent solutions. Digitalization is also radically transforming the powertrains in electric vehicles (EVs). For example, in the battery domain, the batteries' architectures are optimizing the cables to the sensors and sensing point. Innovations like smart battery cells assembled in complex battery systems, with wireless communication between the smart cells and the central battery management system (BMS), enable ultra-high-speed interaction with the smart battery cell parameters. The article presents ECAS vehicles' evolution towards domain controller, zonal vehicle, and federated vehicle/edge/cloud-centric based on distributed intelligence at the vehicle and infrastructure level architectures and the role of AI techniques and methods to implement the different autonomous driving and optimization functions for sustainable green mobility.